Innovations in Open and Flexible Education (Education Innovation Series,, 2018)
This book covers a broad range of innovations in education, such as flipped classrooms, the educational use of social media, mobile learning, educational resources and massive open online courses, as well as theoretical discussions and practical applications in the use of augmented reality and educational technology to improve student engagement and pave the way for students' future studies and careers. The case studies and practical applications presented here illustrate the effectiveness of new modes of education in which the latest technologies and innovations are widely used in the global context. Accordingly, the book can help develop readers' awareness of the potential these innovations hold, thus expanding their expertise and stimulating critical thinking as to how new technologies have made learning and teaching easier in various educational settings.